2021
DOI: 10.1002/cnr2.1466
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant lenvatinib for inoperable thyroid cancer: A case report and literature review

Abstract: Background: Poorly differentiated thyroid cancer (PDTC) is now classified as a separate thyroid tumor entity. It has male predominance and poor prognosis compared to differentiated TC.Case: We report a case of a patient with PDTC who was previously deemed inoperable. A trial of neoadjuvant lenvatinib therapy was given to the patient after that the tumor become operable and the surgery went successfully.Conclusions: Lenvatinib is a feasible option in patients with inoperable TC and can stabilize the lesion size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Unlike in DTC [ 123 , 124 ], RAI appears to be relatively ineffective in the control of distant metastases in PDTC; thus, it is reasonable to consider the use of RAI for metastatic/advanced disease that demonstrates definite iodine uptake [ 125 , 126 ]. Likewise, most cases in our review received at least one cycle of RAI treatment, even without detectable metastatic foci [ 38 , 39 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 73 , 74 , 75 , 80 , 81 , 82 , 85 , 86 , 87 , 88 , 90 , 91 , 97 , 99 , 101 , 102 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in DTC [ 123 , 124 ], RAI appears to be relatively ineffective in the control of distant metastases in PDTC; thus, it is reasonable to consider the use of RAI for metastatic/advanced disease that demonstrates definite iodine uptake [ 125 , 126 ]. Likewise, most cases in our review received at least one cycle of RAI treatment, even without detectable metastatic foci [ 38 , 39 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 73 , 74 , 75 , 80 , 81 , 82 , 85 , 86 , 87 , 88 , 90 , 91 , 97 , 99 , 101 , 102 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ...…”
Section: Discussionmentioning
confidence: 99%
“…Since cytological diagnosis of PDTC based on FNAC is challenging, our review has shown that some patients underwent a hemithyroidectomy or subtotal thyroidectomy with a completion thyroidectomy after histological diagnosis [ 38 , 44 , 52 , 54 , 59 , 65 , 69 , 85 , 103 , 104 , 107 , 108 , 115 , 117 ], but the majority of them were submitted to a total thyroidectomy as the initial operation [ 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 72 , 73 , 75 , 79 , 80 , 81 , 82 , 85 , 86 , 88 , 89 , 90 , 91 , 92 , 93 , 95 , 96 , 100 , 101 ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising and possible strategy reported by several clinical cases 13 and that is being tested in several clinical trials (Table 1 ) is the use of MKIs for neoadjuvant treatment of thyroid cancer. However, more robust data are needed for standardization in clinical practice.…”
Section: Current Situation and Treatment Recommendationsmentioning
confidence: 99%
“… 5–7 However, neoadjuvant therapy remains in the exploratory stages for thyroid cancer. 8 9 At present, multitarget tyrosine kinase inhibitors are the main drugs for the treatment of advanced iodine-resistant differentiated thyroid cancer, and of these drugs, lenvatinib and sorafenib have been recommended in China. Neoadjuvant therapy with these two drugs in LATC has also been reported.…”
Section: Introductionmentioning
confidence: 99%